7 - Qui représente qui ? Choix organisationnels, identités sociales et formation d’une élite forestière au Cameroun: by Samuel Efoua - Oyono, Phil René (Africa Development, 2021)
Representation is one of the parameters of the local ownership of forest mana- gement decentralization in Cameroon. Community representation under Cameroon’s forest management laws is based on village management committees with given responsibilities and powers. This article derives from a study of environmental representation in Southern Cameroon over the last three years. The article shows how environmental representation was built up through the non-democratic and non-competitive selection of management committee members. The article also shows the capture of numerous management committees, reflecting the self-seeking behaviors of their members’ involvement in decentralized management. The authors conclude that current arrangements do not produce effective environmental representation and rural democracy, for the committees do not account downwardly to the population. They therefore propose measures to improve representation and to orient the committees to be more responsive.